Dairy intensification, mothers and children: an exploration of infant and young child feeding practices among rural dairy farmers in Kenya. Issue 1 (14th August 2013) - Wyatt, Amanda J.; Yount, Kathryn M.; Null, Clair; Ramakrishnan, Usha; Webb Girard, Aimee
Abstract Agricultural strategies such as dairy intensification have potential to improve human nutrition through increased household food security. Increasing dairy productivity could also adversely affect infant and young child feeding (IYCF) practices because of increased maternal stress, demands on maternal time, and beliefs about the timing and appropriate types of complementary foods. Yet, few studies have looked rigorously at how interventions can affect young children (0–60 months). The study explores, within the context of rural dairy farming in Kenya, the relationship between level of household dairy production and selected IYCF practices using a mixed‐methods approach. Six focus group discussions with women involved in dairy farming investigated their attitudes towards breastfeeding, introduction of complementary foods and child diets. Ninety‐two households involved in three levels of dairy production with at least one child 0–60 months participated in a household survey. Quantitative results indicated that women from higher dairy producing households were more likely to introduce cow's milk to infants before they reached 6 months than women from households not producing any dairy. Themes from the focus group discussions demonstrated that women were familiar with exclusive breastfeeding recommendations, but indicated a preference for mixed feeding of infants. Evidence from this study can inform nutrition education programmes targeted to farmers participating in dairy interventions in rural, low‐income settings to minimise potential harm to the nutritional status of children.